2015
DOI: 10.1089/ten.tea.2014.0357
|View full text |Cite
|
Sign up to set email alerts
|

Murine and Human Tissue-Engineered Esophagus Form from Sufficient Stem/Progenitor Cells and Do Not Require Microdesigned Biomaterials

Abstract: Purpose: Tissue-engineered esophagus (TEE) may serve as a therapeutic replacement for absent foregut. Most prior esophagus studies have favored microdesigned biomaterials and yielded epithelial growth alone. None have generated human TEE with mesenchymal components. We hypothesized that sufficient progenitor cells might only require basic support for successful generation of murine and human TEE. Materials and Methods: Esophageal organoid units (EOUs) were isolated from murine or human esophagi and implanted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…When mucosal epithelial cells from oral biopsy [40] or esophageal organoid units following digestion of rat esophagi [15,41] were implanted, the scaffolds did not support morphogenesis. These investigators found that in order to create a functional esophageal replacement, both epithelial and muscle cells must be seeded prior to implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When mucosal epithelial cells from oral biopsy [40] or esophageal organoid units following digestion of rat esophagi [15,41] were implanted, the scaffolds did not support morphogenesis. These investigators found that in order to create a functional esophageal replacement, both epithelial and muscle cells must be seeded prior to implantation.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators found that in order to create a functional esophageal replacement, both epithelial and muscle cells must be seeded prior to implantation. We adapted protocols from previous studies [15,41] to isolate native esophageal cells and cultured them on a synthetic scaffold in a bioreactor with commercial epithelial media injected into the lumen and commercial smooth muscle media bathing the abluminal surface. Each cell type was successfully enriched in their respective medium following 14 days in culture.…”
Section: Discussionmentioning
confidence: 99%
“…As the esophagus is an organ with multiple cellular origins and no clear stem cell niches have been defined, these organoids provide a complex cell source allowing for regeneration of all layers. The organoids proliferated in the scaffold in vitro ; when implanted in vivo , these substitutes regenerated all layers of the esophagus . In a recent study using a porcine model, La Francesca et al .…”
Section: Full‐thickness Esophageal Te Using Scaffolds and Stem Cellsmentioning
confidence: 99%
“…Tissue engineering of the esophagus has been described in multiple reports (Spurrier et al 2014b;Chian et al 2015); however, little is known about the esophageal stem cells that make this possible (DeWard et al 2014). Esophageal organoids can be cultured with exogenous Wnt agonists and the BMP antagonist Noggin, both required for stem-cell self-renewal (DeWard et al 2014).…”
Section: Esophagusmentioning
confidence: 99%
“…However, this was in the context of a focal defect rather than a circumferential esophageal interposition. Generation of full thickness esophagus from both murine and human tissue, complete with the critical components for function-regenerating epithelium, smooth muscle, and an ENS-has been reported more recently (Spurrier et al 2014b). This report includes evidence that the esophageal organoid units, which are transplanted to form the engineered esophagus can be maintained in culture and also preserved after vitrification.…”
Section: Esophagusmentioning
confidence: 99%